A Ciceronian mirage? Cicero's portrait as provincial governor through his letters - Díaz-Fernández, Alejandro (My University, 2019)
Cicero’s writings undoubtedly are an essential source for studying numerous aspects of the Late Republic and, particularly, of the Roman administration at the end of the first century BC. More concretely, his letters constitute our main source for knowing how Roman command worked in the provinces, presenting us at the same time a valuable portrait of the role played by the own orator during his stay in Cilicia as proconsul. However, whether this image corresponds to the reality of his government and, particularly, to the traditional standards of the Roman provincial administration is debatable. It seems no casual that Cicero’s portrait as proconsul essentially agrees with the ideal of government presented by him in the letter sent to his brother Quintus during the latter’s command in Asia as proconsul (Cic. Q. fr. 1.1). As several scholars have stressed, many of the virtues quoted in the letter seems related to the philosophical doctrines about the ideal ruler rather than to the day to day of a Roman commander in his province. Recent studies have pointed out indeed that Cicero’s command in Cilicia was directly influenced as well by stoic doctrines, to the point of concluding that the orator was selected to govern Cilicia in 51 (under the lex Pompeia of 52) to serve as exemplum of provincial administration. Nonetheless, beyond his philosophical principles, it seems clear enough that Cicero’s intention was to create a positive portrait of his provincial command through his letters: we should keep in mind that the preservation of Cicero’s works necessarily determines our knowledge of the Late Republic and, especially, of his own role in Cilicia, so we run the risk of basing our conclusions about the Roman provincial administration on a ‘Ciceronian mirage’. Thus, the main aim of this paper is to determine to what extent Cicero’s own image as proconsul is a reliable portrait of the Roman provincial government at the Late Republic.
Keywords: Cicero; Ancient Rome; Roman Provinces; Roman Republic